'Seeing me through my memories': a grounded theory study on using reminiscence with people with dementia living in long‐term care. Issue 23 (12th July 2014) - Cooney, Adeline; Hunter, Andrew; Murphy, Kathy; Casey, Dympna; Devane, Declan; Smyth, Siobhan; Dempsey, Laura; Murphy, Edel; Jordan, Fionnuala; O'Shea, Eamon
<x xml:space="preserve">Abstract</x> Aims and objectives To understand people with dementia, staff and relatives perspectives on reminiscence, its impact on their lives and experience of care and care giving. Background The quality of life of people with dementia living in long‐term care is an important question for providers and policymakers. Reminiscence is thought to have potential for increasing resident–staff interaction, thereby contributing to enhanced personhood for people with dementia. Relatively little is known about the effects of reminiscence on people with dementia or staff. Design This is a grounded theory study. This design was chosen because of its focus on understanding people's behaviour, interaction and response to events. Methods In‐depth interviews were conducted with residents with dementia (n = 11), relatives (n = 5), healthcare assistants (n = 10), nurses (n = 9) and nurse managers (n = 3). Results Reminiscence enabled staff to see and know the person beneath the dementia. It acted as … a key revealing the person to staff, enabling them to engage with the person with dementia in a different way. Knowing the person enabled staff to understand (through the lens of the person's past) and sometimes to accommodate the person's current behaviour. Conclusion The theory of 'seeing me (through my memories)' was generated from the data. This theory explains that through reminiscing and engaging with the person with dementia, staff begin to see the person (their personhood) through the mirror of their memories. Relevance to clinical practice This study found that reminiscence enhanced the experience of living in long‐term care for residents with dementia and working in long‐term care settings for staff.